DETERMINATION OF PHYTOCHEMICAL COMPOSITION AND TEN ELEMENTS CONTENT (CD, CA, CR, CO, FE, PB, MG, MN, NI AND ZN) OFCARDARIA DRABA BY GC-MS, FT-IR AND AAS TECHNIQUES - HAIDER MASHKOOR HUSSEIN (International Journal of Pharma and Bio Sciences, 2016)
The research objectives were to investigate the phytochemical composition of the methanolic leaves extract of Cardaria draba and its elements content. GC-MS analysis revealed the existence of the8- Hydroxy-2-octanone, Phosphorothioic acid , S-ester with trimethylenediiminodipropa,Pyrrolidine1,1’methylenebis,N[4Aminobutyl]aziridine,Cycloheptane,1,2dimethoxy,trans,N[3[NAziridyl]propylidene]tetrahy drofurfuralamine, o-Cymene, 1,13-tetradecadien-3-one, 5-Octadecenal, 2,6-Nonadienal , (E,Z), Piperidine , 1-(1-propenyl), Imidazole, 2-amino-5-[(2-carboxy)vinyl],S-Benzyl-l-cysteinyl-S-tetrahydropyranyl-lcysteinylhydrazide,β-D-Glucopyranose,1-thio-,1-Nhydroxy5(methylthio)pentar,9Oxabicyclo[3.3.1]nonane- 2,6-diol, Formamide ,N-methyl-N-4-[1-(pyrrolidinyl)-2-butynyl], Naphthalene,1,2-dihydro-2,5,8-trimethyl, Pyrrolizin-1,7-dione-6-carboxylic acid, methyl(ester),Cis,-5,8,11,14,17-Eicosapentaenoic acid, Durohydroquinone, N,N’-Pentamethylenebis[s-3-aminopropyl thiosulfuric acid], Phenol ,2,4-dichloro-6- [(1H-indazol-7-ylamino)methyl],(3,3-Dimethyl-5methylthio3,4(2H)dihydropyrrol2ylidene)ace,Corymbolone, Folic acid, Oxiraneundecanoic acid , 3-pentyl-, methyl ester , cis, Benzeneethanamine ,2-isothiocyanato- N-methyl-N-[2.trans, Paromomycin, Cyclodeca[b]furan-2(3H)-one , 9-(acetyloxy)-3a,4,5,8,9,11a-h, 13- Heptadecyn-1-ol, Hexadecanoic acid , 1-(hydroxymethyl)-1,2-ethanediyl ester, l-(+)-Ascorbic acid 2,6- dihexadecanoate, 2,6-Bis[2-[2-S-thiosulfuroethylamino]ethoxy]pyrazine, Dasycarpidan-1-methanol , acetate (ester), 2,7-Diphenyl-1,6-dioxopyridazino[4,5:2’,3’]pyrrolo[4’,5’-d]pyrid, 9,12,15-Octadecatrienoic acid , (Z,Z,Z), and Ethyl iso –allocholate. The FTIR analysis of Cardaria draba leaves proved the presence of Alkenes, Alcohols, Ethers, Carboxlic acids, Esters, Alkanes, Hydrogen bonded Alcohols and Phenols. Several metals were determined in Cardaria drabamedicinal plant by applying Atomic Absorption Spectrophotometer. The obtained results showed that (Cadmium, Calcium, Chromium, Cobalt, Iron, Lead, Magnesium, Manganese, Nickel and Zinc) content in tested plant were (0.998±0.07, 4.020±0.58, 7.350±2.09, 0.660±0.09, 40.000±1.20, 3.000±0.26, 27.300±0.98, 15.022±0.61, 5.990±0.27 and 7.190±0.30) respectively.